2022
DOI: 10.3390/su141610136
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Review on Solar Stills—Latest Developments and Overview

Abstract: This up-to-date and comprehensive literature study provides a rich overview of recent developments in several solar still types. This review examines a large number of theoretical, experimental, and computational studies connected to the single-slope, double-slope, solar still with a condenser, hybrid, and other limited types of solar stills. To make the work more relevant to readers, the authors provide a panoramic view of solar still varieties as well as a complete overview of the most recently published rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 164 publications
0
1
0
Order By: Relevance
“…It is worth mentioning that some of the above three techniques used to enhance solar still performance have been mentioned in several review works on solar stills which appeared in literature during the last decade. These include Muftah et al (2014), Manchanda and Kumar (2015), Kalita et al (2016), Ithape et al (2017), Essa et al (2022), Ayoobi and Ramezanizadeh (2022) and Younis et al (2022) Results reported about increases in still performance metrics using one of the above three particular designs show wide variations. Increases in still efficiencies in the range of 10 -300% have been reported in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that some of the above three techniques used to enhance solar still performance have been mentioned in several review works on solar stills which appeared in literature during the last decade. These include Muftah et al (2014), Manchanda and Kumar (2015), Kalita et al (2016), Ithape et al (2017), Essa et al (2022), Ayoobi and Ramezanizadeh (2022) and Younis et al (2022) Results reported about increases in still performance metrics using one of the above three particular designs show wide variations. Increases in still efficiencies in the range of 10 -300% have been reported in some cases.…”
Section: Introductionmentioning
confidence: 99%